Informal employment in emerging and transition economies - Lehmann, Hartmut; Tatsiramos, Konstantinos; Polachek, S. W. (Research in labor economics ;, 2012)
Informality and informal employment are wide-spread and growing phenomena in all regions of the world, in particular in low and middle income economies. A large part of economic activity in these countries is not registered or under-declared and many workers enter employment relationships that do not provide any or only partial protection, work with little or no physical capital, receive low wages and work under conditions that can be hazardous to their health. This volume sheds light on the incidence and persistence of informality and the role of institutions and government regulations. The articles offer insights into issues such as how labor and tax regulations determine the incidence of informality, whether reforms on tax and other regulations can reduce informal employment, to what extent informality occurs as a result of job separations, how persistent is informal employment, how informal employment can be detected and whether migration can be a substitute for informal employment.